PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PUISI SISWA SEKOLAH DASAR - Rachma Nurfitria; Fitri Nuraeni; Nadia Tiara Antik Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low reading comprehension skills in poetry among elementary school students. The aim of this research was to improve the poetry reading comprehension skills of fourth-grade students through the implementation of the Contextual Teaching and Learning (CTL) model supported by digital flipbook media based on FlipHTML5. The research method used was Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles. Data collection instruments included essay tests based on five reading comprehension indicators, teacher and student observation sheets, and documentation. The results showed a significant improvement in students’ poetry reading comprehension skills after implementing the CTL model with flipbook media. Based on these findings, the CTL model supported by flipbook media is effective as a learning strategy for enhancing poetry reading comprehension